Fracture model for predicting tensile strength and fracture toughness of concrete under different loading rates. (15th February 2023) - Yang, Shutong; Wang, Mingxin; Lan, Tian; Liu, Shutong; Sun, Zhongke
Highlights: Fracture behaviors of concrete under different loading rates are clarified. Material heterogeneity and discontinuity are indicated in fracture modelling. Size-independent fracture parameters under different loading rates are obtained. Scatters in predicted fracture parameters are analyzed through statistical analysis. Rate dependences of tensile strength and fracture toughness are clarified rationally. Abstract: For the sake of safety evaluation of concrete structures under dynamic loading conditions, the rate dependences of concrete fracture parameters are necessary to be elucidated rationally first. Therefore, the aim of this study is to develop a fracture model for determining the size-independent tensile strength ( f t ), the fracture toughness ( K IC ) and the fracture energy ( G F ) under different loading rates. The fracture mechanism was analyzed comprehensively using three-point bending tests on concrete beams with varied depths ( h ) and ratios of the initial crack length to the beam depth ( a 0 / h ). As the loading rate increases, the number of fractured coarse aggregates is increased, and the shape of the load–displacement curve around the maximum fracture load ( F max ) becomes sharper. Subsequently, a fracture model was proposed to predict the size-independent parameters f t, K IC and G F by incorporating the average aggregate size ( d avg ) and a discrete coefficient ( β ) to indicate material heterogeneity and discontinuity, respectively. The critical effective crack length (Δ a c ) was discretized and quantified as d avg multiplied by β . Closed-form solutions of f t, K IC and G F were obtained using F max based on the boundary effect model. f t, K IC and G F can be explicitly predicted after determining F max from the fracture tests, and were generally irrelevant to h and a 0 / h under individual loading rates, indicating their size-independence. The scatters in the f t, K IC and G F values were determined using a statistical analysis. The rate dependences of the fracture parameters were clarified quantitatively through elucidating the variations in f t, K IC and G F with respect to the loading rate. Moreover, the predicted fracture parameters based on the proposed model were insensitive to the possible variations of d avg and β . This study brings a new insight into the fracture behaviors of concrete under different loading rates and provides scientific guidance for the disaster prevention of concrete structures.